Polymerase chain reaction based detection of banana bunchy top virus(BBTV) and banana streak virus(BSV) - Ponsubrya R K (Department of Plant Biotechnology, College of Agriculture, 2008)
Banana is an important fruit crop of Kerala. It is affected by various diseases including viral diseases, of which Banana Bunchy Top Virus (BBTV) and Banana Streak Virus (BSV) assume economic importance. Detection of these viruses in early stage warrants great significance. The present study entitled “Polymerase Chain Reaction based detection of Banana Bunchy top virus (BBTV) and Banana streak virus (BSV)’’ was taken up in this context. It was carried out at the Department of Plant Biotechnology, College of Agriculture, Vellayani, Thiruvananthapuram during October 2006 to July 2008 with the objective of developing a protocol for the detection of these two DNA viruses of banana using polymerase chain reaction (PCR) technique.